Increased Agricultural Literacy through the Bacterial Consortium Production Based on IoT Temperature Sensors for Students at SMKN 1 Purwosari: Peningkatan literasi pertanian melalui produksi konsorsium bakteri berbasis IoT sensor suhu pada siswa SMKN 1 Purwosari - Dani Septia, Erfan; Maftuchah , Maftuchah; Zakia , Aulia; Maulana Zulfan, Iqbal; Oktafian, Akhmad Rizal; Putra, Sohnif Nurwicahyo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aims to enhance the understanding of Vocational High School (SMK) students in sustainable agriculture, particularly in producing bacterial consortiums of Biofertilizer and Bioprotectant. Situation analysis reveals that SMK students face challenges in accessing training, limited resources and facilities, and a lack of awareness regarding the importance of sustainable farming practices. The program presents strategic solutions, beginning with developing a comprehensive learning module on sustainable agriculture and utilizing bacterial consortiums, biofertilizers, and bioprotectants. This module is designed to assist students in comprehending the concepts, benefits, and practical applications of sustainable farming. The solution also includes practical field training, especially in the propagation of bacterial consortiums, utilizing IoT temperature sensor DS18B20 to monitor the propagation process. The anticipated outcome of this program is an improvement in sustainable agricultural literacy among SMK students. The expectation is that they will better understand the concepts of sustainable agriculture and the implementation of bacterial consortiums, biofertilizers, and bioprotectants. Additionally, students are expected to acquire practical skills in the propagation of bacterial consortiums. Thus, the program aims to positively contribute to developing students' skills and encourage active participation in sustainable agriculture.